Integrated metabolomics and lipidomics analyses suggest the temperature-dependent lipid desaturation promotes aflatoxin biosynthesis in Aspergillus flavus - Wu, Shaowen; Huang, Wenjie; Wang, Fenghua; Zou, Xinlu; Li, Xuan; Liu, Chun-Ming; Zhang, Wenyang; Yan, Shijuan (Frontiers in Microbiology, 2023)
Temperature is one of the main factors affecting aflatoxin (AF) biosynthesis in Aspergillus flavus. Previous studies showed that AF biosynthesis is elevated in A. flavus at temperatures between 28°C-30°C, while it is inhibited at temperatures above 30°C. However, little is known about the metabolic mechanism underlying temperature-regulated AF biosynthesis. In this study, we integrated metabolomic and lipidomic analyses to investigate the endogenous metabolism of A. flavus across six days of mycelia growth at 28°C (optimal AF production) and 37°C (no AF production). Results showed that both metabolite and lipid profiles were significantly altered at different temperatures. In particular, metabolites involved in carbohydrate and amino acid metabolism were up-regulated at 37°C on the second day but down-regulated from days three to six. Moreover, lipidomics and targeted fatty acids analyses of mycelia samples revealed a distinct pattern of lipid species and free fatty acids desaturation. High degrees of polyunsaturation of most lipid species at 28°C were positively correlated with AF production. These results provide new insights into the underlying metabolic changes in A. flavus under temperature stress.